The Formation of Variation Contracts in New Zealand: Consideration and Estoppel - Roberts, Marcus (Victoria University of Wellington Law Review, 2016)
This article will review the current New Zealand approach to the formation of variation contracts. In particular, it will critique the current position taken by the Court of Appeal that either: a practi-cal benefit can be good consideration;, or consideration is not needed for variation agreements. The article will then explore some of the implications of using estoppel as an alternative basis to enforce variation agreements when consideration has not been provided by the promisee.